An approach for improving flood risk communication using realistic interactive visualisation. (16th August 2016) - Kuser Olsen, V.B.; Momen, B.; Langsdale, S.M.; Galloway, G.E.; Link, E.; Brubaker, K.L.; Ruth, M.; Hill, R.L.
Abstract : Floods become disasters when people and property are placed in harm's way. Yet stakeholders, those at risk of flooding, often take no action to reduce their vulnerability. We demonstrated an approach for improving flood risk communication using the process of realistic interactive visualisation. Our goal was to communicate information about flood risk at the community level and increase stakeholders' intent to take actions to reduce their risk. Realistic visualisation promotes action based on emotional connection to images. Interactive visualisation is the direct construction of the model by stakeholders. As a reference, we also tested a nationally‐recognised model designed for the U.S. Federal Emergency Management Agency (FEMA). Both methods resulted in significant learning about community‐specific flood risk and risk reduction options. To maximise the intent by stakeholders to take actions to reduce risk, the realistic interactive visualisation method used in high‐quality meeting facilities performed best.